Symmetry of scalar second-order stochastic ordinary di®erential equations: Boonlert Srihirun - Team, Support (Thai Journal of Mathematics, 2008)
In this manuscript, the definition of an admitted Lie group for stochastic differential equations given in [1] is applied to second-order ordinary stochastic differential equations. Admitted Lie group generators for a variety of equations are obtained.